Keratoconus Epidemiology Presentations at Najran Province, Saudi Arabia - Alzahrani, Khaled (Clin Optom (Auckl), 2021)
AIM: Our study aims to produce an estimation of the keratoconus disease epidemiology and important demographic factors in disease presentation in Najran city in the south of Saudi Arabia. METHODS: Keratoconus patients between 9 and 29 years of age at the eye clinic of King Khaled General Hospital in Najran Province with a confirmed diagnosis of keratoconus were recruited over one year period. Visual acuity, keratometry, corneal thickness and demographic data were collected and analysed. RESULTS: The keratoconus prevalence in Najran Province was found to be 87.3 cases per 100,000 people with an incidence of 28.47 per 100,000 cases. The disease presented more frequently in male patients (67.9%) with a statistically significant difference in the mean age between genders (p=0.014). Most cases presented at a moderate stage, and almost half of the cases reported a family history of the disease. There were statistically significant differences in best visual acuity and corneal thickness between genders (p<0.05). The majority of the cases were managed with contact lenses (56.08%). CONCLUSION: Genetic and environmental factors could have a substantial role in the increased rate of keratoconus presentation in Najran Province. Screening programmes should dedicate more attention to late presentation to improve prevention and early detection. More studies on keratoconus epidemiology in Saudi Arabia are needed.